Letter to Jane Tolmach from Dan A. Kimball - Dan A. Kimball:::::: (1960)
A letter to Jane Tolmach from Dan Kimball, President of Aerojet-General Corporation, that discusses his role as the Chairman of the Los Angeles Citizens Committee and their efforts to raise money to host the Convention in Los Angeles in 1960.